2007
DOI: 10.1369/jhc.6a7144.2007
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Neuronal Apoptosis Inhibitory Protein in Human Tissues

Abstract: The neuronal apoptosis inhibitory protein (NAIP) gene, also known as the baculovirus inhibitor of apoptosis repeat-containing protein 1 (BIRC1) gene, is a member of the inhibitors of apoptosis (IAP) family and was first characterized as a candidate gene for spinal muscular atrophy (SMA). The expression of NAIP has been thoroughly studied in the central nervous system and overlaps the pattern of neurodegeneration in SMA. Recent studies have pointed to a role for NAIP in non-neuronal cells. We report here the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…An earlier study of NAIP distribution in human tissues36 showed a particularly intense staining in the small intestine epithelium. Based on these results, the further characterization of NAIP by confocal microscopy in the human epithelial carcinoma cell line HeLa, was undertaken and unexpectedly demonstrated the presence of NAIP in the central spindle (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…An earlier study of NAIP distribution in human tissues36 showed a particularly intense staining in the small intestine epithelium. Based on these results, the further characterization of NAIP by confocal microscopy in the human epithelial carcinoma cell line HeLa, was undertaken and unexpectedly demonstrated the presence of NAIP in the central spindle (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Standardized amounts of protein samples (25  μ g to 50  μ g) were separated by 10% SDS-PAGE. Proteins were subsequently transferred onto nitrocellulose membrane and incubated in blocking solution (PBS, 5% nonfat milk, 0.2% Tween-20) for 1 hour at room temperature followed by overnight incubation with the NAIP-J236 rabbit polyclonal antibody at 4 °C diluted at 1:1500. Membranes were washed with PBS-T (PBS, and 0.2% Tween-20) 3 times followed by incubation with secondary antibody (anti-rabbit or mouse; Cell Signaling) for 1 hour at room temperature at the dilution suggested by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…It is plausible that mNaip5 binds to caspase-3 and -7 and/or uses procaspase-9 sequestration to block the activation of APAF-1 apoptosome, as human NAIP does [5,6]. Human NAIP is predominantly expressed in macrophage cells of the lung and spleen [30], suggesting that human NAIP protects macrophage cells from apoptotic cell death in these human tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In human lung and spleen tissue, human NAIP is predominantly expressed in macrophage cells [30], suggesting that it is involved in their survival. This study demonstrates the dual role of human NAIP, and also of mNaip5, in macrophage survival, leading to cell death caused by L. pneumophila infection and protecting from apoptosis induced by DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…NAIP is highly expressed in intestinal villi (23) and evidence is emerging for it being an intracellular pathogen receptor, chiefly for flagellin. Although none of bacteria in this study are flagellated, past work has shown NAIP modulation lies downstream of the TNF pathway (24) and it may be that probiotic modulation of TNF-␣ (25) elicited the IAP elevation observed in our animals.…”
Section: Discussionmentioning
confidence: 99%